Os significados dos discursos ecologicamente corretos - Bartmanovicz, Luciane Lucyk (2010)
This work intends to discuss about the discourse ecologially correct from publicity ads showed in the televise media. The choice of ecology and marketing argumentation was made because of the increasing number of products using this approach in different media, mainly the television. The main objectives of this work are: to demonstrate how the advertisements dialogue between themselves, how they are formed, what differentiate them and what sense effect they produce; to verify the discursive meanings from de marketing ads in two perspectives: the ecological discourse used for a specific purpose, that is, the divulgation concerning the environmental conservation and the everyday changing habits about the usage of natural resources; second, the marketing speech used as a resource to the spreading of consumption products, which purpose is the profit, assuming an apparent environmental concerning and a conscious consumption. In order to do this research, it was used the Greenpeace and WWF-Brazil NGO advertisements, with the objective of discuss about the advertisement as an ecological alert, and for the advertisements of the Grendene, Ypê and Natura companies it was discussed about the ecological discourse as a marketing tool.